Organizing social contextual information for display on mobile devices. - Tan, Meng Yoke. (2012)
Users are increasingly overwhelmed with information as they embrace the hugely popular and successful social media as a means to create and use it. There is a rising concern on organization and display of information on mobile devices to meet users’ satisfaction. The multimodal capability, small screen size and limited interactivity of mobile devices have prompted researchers and designers to focus on the use of context as a means to filter and show only relevant and useful information to their users. However, the small screen size of mobile devices poses a number of design challenges in the provision of services to users. Using tourism as the domain, this thesis looks at such challenges in an attempt to overcome the problem of organizing and displaying information so as to deliver more effective services and functions to users. This thesis attempts to address three issues: First, there is a lack of consensus in defining context and an understanding of users’ goals. To study this, the thesis includes a literature review of existing research; a focus group to gather users’ information needs for commonly executed tasks by tourists; a participatory design group to gather ideas on value-added features and preferred screen design; and a quantitative survey to determine tourists’ information needs and their different preferences by tourist groups. As part of the findings, the TILES (Temporal, Identity, Location, Environment and Social) model was proposed to define and classify five main contextual types, and the properties associated with each type for tourism-related applications.